Pengaruh Akuisisi Terhadap Performa Finansial Pada Perusahaan di Bursa Efek Indonesia (International Forum of Researchers and Lecturers, 2024)
The purpose of this observation is to determine the impact of acquisitions on the financial performance of companies that implement acquisition strategies listed on the IDX. To assess a company's financial performance, comparisons are usually used, including: Comparison of current assets with current debt, comparison of total debt with total assets, and comparison of net profit after tax with sales. The literature review method is applied in this observation which is carried out by reviewing the results of past observations that are in line with this topic, but there are inconsistent outcomes. Observations applied by (Utari, Asriany, and Hamid 2022) which state that in acquiring companies they must be able to assess the financial performance of target companies so that the risk of loss will be reduced. While the observations applied by (Firdaus and Dara 2020) provide information that there is no change in the company's financial performance after the acquisition, the company's financial performance remains stable between pre and post acquisition. Based on this explanation, this observation was chosen to determine the impact of acquisitions on the financial performance of companies with acquisition strategies listed on the IDX.